Ceritinib efficacy in SMARCA4-deficient NSCLC harboring novel CTNND2 ALK/EML4-ALK fusion: case report - Fu, Zhigang; Huang, Gengda; Xie, Jian; Luo, Li; Ren, Qinqin; He, Hong; Wang, Yuan; Zhang, Jiexia (Frontiers in Oncology, 2026)
SMARCA4-deficient non-small cell lung cancer (SMARCA4-dNSCLC) is an aggressive malignancy with poor prognosis, rarely harboring EGFR, ALK, or ROS1 alterations. We report an advanced SMARCA4-dNSCLC case with brain metastasis exhibiting a novel CTNND2-ALK/EML4-ALK double-fusion. Following platinum-based chemotherapy and brain radiotherapy, next-generation sequencing identified the dual fusions (abundances: 2.6% and 5.2%), confirmed by ALK protein expression. The patient subsequently received ceritinib (750 mg/day). After 3 months, targeted lesions regressed significantly, and progression-free survival exceeded 24 months with ongoing response. This demonstrates efficacy of the ALK inhibitor ceritinib in ALK-rearranged SMARCA4-dNSCLC and underscores the clinical value of genomic-guided therapy.